Domestic bureaucratic politics and Chinese foreign policy - Lai, Hongyi; Kang, Su-Jeong (Taylor & Francis, 2014)
One of the outstanding features of China’s domestic politics is the prominence of the bureaucracy in the policy-making process. Arguably, bureaucracy is the next major player in the policy-making process in China after the top leaders. In this article, the three following aspects of the role of bureaucracy in the Chinese foreign policy-making process are examined: (1) the structure of the bureaucracy, especially the main agencies of the bureaucracy involved in foreign policy making; (2) the respective responsibilities of these agencies and their roles in the process; and (3) inter-agency coordination including the resolution of conflict among them. It observes that while the Ministry of Foreign Affairs plays a key role in the process, other ministries and bureaucratic agencies have significant and even growing input in an increasing number of functional areas, such as trade, finance, economy, climate change, soft power and military affairs. In addition, coordination among these agencies has become a key in the policy-making process.